2011
DOI: 10.4061/2011/716871
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Parkinson's Disease

Abstract: Parkinson's disease (PD) is a progressive, neurodegenerative condition that has increasingly been linked with mitochondrial dysfunction and inhibition of the electron transport chain. This inhibition leads to the generation of reactive oxygen species and depletion of cellular energy levels, which can consequently cause cellular damage and death mediated by oxidative stress and excitotoxicity. A number of genes that have been shown to have links with inherited forms of PD encode mitochondrial proteins or prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
97
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 199 publications
(259 reference statements)
4
97
0
2
Order By: Relevance
“…Increasing evidence implicates mitochondria in the pathogenesis of PD. 5 Here, we analyzed the expression patterns of mitochondrial respiratory chain subunits of PPN neurons, finding a significant decrease in expression of mitochondrial proteins in cholinergic neurons, suggestive of mitochondrial injury. A similar decrease in expression was seen for voltage…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence implicates mitochondria in the pathogenesis of PD. 5 Here, we analyzed the expression patterns of mitochondrial respiratory chain subunits of PPN neurons, finding a significant decrease in expression of mitochondrial proteins in cholinergic neurons, suggestive of mitochondrial injury. A similar decrease in expression was seen for voltage…”
Section: Discussionmentioning
confidence: 99%
“…2 Although the precise cellular and molecular mechanisms underlying this neuronal death remain unknown, several reports implicate an underlying mitochondrial dysfunction, relating to energy deficits, enhanced production of free-radical species with concomitant oxidative stress, 3 proteasomal deregulation, 4 and neuronal excitotoxicity. 5 Evidence for a mitochondrial-related cause in PD stems from studies reporting on the use of human postmortem brains of patients with PD, which found a deficiency of complex I of the mitochondrial respiratory chain in the SNpc. 6 Furthermore, outside the central nervous system a mitochondrial respiratory chain complex I deficiency has also been detected in the blood platelets of patients with PD, with some patients who also displayed defects of mitochondrial respiratory chain complexes II and III.…”
mentioning
confidence: 99%
“…MPTP's neurotoxicity is mainly due to its active metabolite, 1-methyl-4-phenylpyridinium ion (MPP + ), which can be taken up by neurons via dopamine transporters, and causes neuronal damage [5]. MPP + reacts with mitochondria complex I of the electron transport chain and leads to damage of the mitochondrial membrane, collapse of the mitochondrial membrane potential, irreversible oxidative damage, and activation of the apoptotic cascade [6][7][8][9]. Mitochondrial complex I deficiency is one of the major clinical changes in PD patients, pointing toward a critical role of MPP + /MPTP in elucidating the possible pathogenesis mechanisms of neurodegenerative diseases [10,11].…”
mentioning
confidence: 99%
“…Mitochondrial dysfunction increases over time and is observed as an accumulation in reactive oxygen species (ROS), as decreases in synthesis of electron transport chain proteins and ATP production, and/or as changes in mitochondrial size, shape, and membrane potential. This dysfunction has been linked to aging [1][2][3] and a host of age-related diseases including Parkinson's [4], Alzheimer's [5,6], diabetes [7], and others [8,9]. Recent studies have also shown that patients on long term HIV/AIDS therapy exhibit many mitochondria related diseases including, diabetes, Parkinson's, and Alzheimer's [10,11].…”
Section: Introductionmentioning
confidence: 99%